Implementasi sila keadilan sosial dalam kebijakan ekonomi di Indonesia - asshiddiq, muhammad thoriq (Maliki Interdisciplinary Journal, 2025)
The COVID-19 pandemic has had a significant impact on the national economy, particularly in terms of social inequality and public welfare. In this context, the fifth principle of Pancasila, Social Justice for All the People of Indonesia, serves as a fundamental paradigm in formulating post-pandemic economic policies. This study aims to examine the application of social justice values in the formulatoin of economic policies oriented toward equity, sustainability, and shared prosperity. The discussion method is employed by reviewing various literature, regulations, and national economic policies issued after the pandemic. The results of the discussion indicate that the paradigm of social justice requires a balance between economic growth and the equitable distribution of development outcomes, particularly through fiscal policies, targeted subsidies, and support for MSMEs and community based economies. In addition, strengthening community based economic systems and implementing distributive justice are crucial to realizing an open and sustainable economy. Therefore, the principle of social justice serves as both a philosophical foundation and a strategic direction in building a fair, resilient, and equitable national economy in the post-pandemic era.